If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 19 + 20 = 4 + 5x Reorder the terms: 19 + 20 + -10x = 4 + 5x Combine like terms: 19 + 20 = 39 39 + -10x = 4 + 5x Solving 39 + -10x = 4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 39 + -10x + -5x = 4 + 5x + -5x Combine like terms: -10x + -5x = -15x 39 + -15x = 4 + 5x + -5x Combine like terms: 5x + -5x = 0 39 + -15x = 4 + 0 39 + -15x = 4 Add '-39' to each side of the equation. 39 + -39 + -15x = 4 + -39 Combine like terms: 39 + -39 = 0 0 + -15x = 4 + -39 -15x = 4 + -39 Combine like terms: 4 + -39 = -35 -15x = -35 Divide each side by '-15'. x = 2.333333333 Simplifying x = 2.333333333
| 0=5v+30 | | 3(1-4v)+5=104 | | 2t-18=0 | | 24x-6=24x+36 | | 0=7v+26 | | ln(x)+2=0 | | -8=t-2 | | 4(4x-2.2)=2x-8.8 | | 7(1+2a)=-105 | | 22x+13=-18x+13 | | ln(2x+1)ln(9-4x)=0 | | ln(2x-1)ln(9-4x)=0 | | 7(x-7)=-98 | | x+4=x-9 | | 17=-6v-2 | | -6=-8m+8-6 | | -(3m-8)=12-m | | -5n+6n=2 | | 5m-4m=8 | | -2x+8x=-18 | | 9=-12t+3 | | 5y-6=2y-30 | | a+b=21 | | -13=-2y+7 | | -12t-3=9 | | -(3m-8)=13-m | | 6(x-3)+3=2x+4(-3+x) | | 3(4x-6)=2(6x+3) | | (-8x-5)=(-2-7x) | | 2x+[2x-(x-4)]=-[-(5-x)] | | 8x-3(2x-3)=-4(2-x)+3(x-4)-1 | | 6(x-3)=3+6x+3x |